Component and Syntactic Renewals of Idioms in Comics of Miki Muster (Preučevanje otroške in mladinske književnosti, 2025)
Comics as stories, shown with a sequence of images and with text usually in speech bubbles, represent a rich source of linguistic and stylistic peculiarities: foreign language elements, occasionalisms, word games, irony, onomatopoie, stylistically marked words and idioms. In this paper, we focus on idioms in selected comics of Miki Muster. In many comics it is a matter of renovating one of the well-known phrases, which are sufficiently obvious and recognizable that we can understand original form. The collected examples contain innovative interventions in idioms, which, due to their originality and humor, attract the addressee's attention. Aware that phraseological renovations in the text have a very special effect, in the paper, we observe single-level, multi-level and crossing renovations, and we think about their purpose and effect in the texts; idioms with renovation better fit the time and environment of the comic story or emphasize the speech peculiarities of the characters.